Assessment of the Effects of Breastfeed and Bottle Feed on Health in Children - Ramzan, Humaira; Parveen, Fozia; Parveen, Sadaf; Rehman, Aqsa; Mushtaq, Khudija; Saeeda, Khawer (Biological and Clinical Sciences Research Journal, 2025)
Infant feeding practices play a critical role in determining childhood health and developmental outcomes. Although the World Health Organization recommends exclusive breastfeeding for the first six months of life, bottle feeding and mixed feeding remain common in low- and middle-income countries, including Pakistan, potentially increasing the risk of childhood morbidity and developmental delay. Objective: To assess the association between breastfeeding, partial feeding, and bottle feeding with childhood illnesses and developmental outcomes among children aged 18 to 36 months attending a tertiary care hospital in Lahore, Pakistan. Methods: This cross-sectional analytical study was conducted in the pediatric unit of Sir Ganga Ram Hospital, Lahore, from March 2025 to August 2025. A total of 384 children aged 18–36 months were enrolled using convenience sampling. Data on feeding practices during the first six months of life, sociodemographic characteristics, childhood illnesses, and developmental outcomes were collected through a structured and validated questionnaire. Cognitive, gross motor, and fine motor development were assessed using standardized developmental tools. Data were analyzed using SPSS version 26. Associations between feeding practices and outcome variables were evaluated using the chi-square test, with p < 0.05 considered statistically significant. Results: Of the 384 children, 43.0% were exclusively breastfed, 43.5% received partial feeding, and 13.5% were bottle-fed. Bottle-fed children had significantly higher rates of pneumonia (69.4%), diarrhea (59.5%), vomiting (67.5%), and seizures (67.2%) compared with breastfed children (p < 0.001). Exclusively breastfed children demonstrated superior developmental outcomes, with 87.9% achieving above-average scores in cognitive, gross motor, and fine motor domains and none scoring below average. In contrast, bottle-fed children showed higher proportions of below-average developmental scores across all domains. Parental or caregiver ratings were consistent with objective developmental assessments (p < 0.001). Conclusion: Exclusive breastfeeding is strongly associated with reduced childhood morbidity and significantly better cognitive and motor development. Bottle feeding is linked to increased infectious illnesses and poorer developmental outcomes. These findings emphasize the need to strengthen breastfeeding promotion and support strategies to improve child health outcomes in Pakistan.